The Effect of Honey Administration on The Histopathology of The Duodenum of Wistar Rats as a Inhibition of The Toxic Effects of Borax (Sodium tetraborate) - Noviana, Dian; Syarifah, Mustika Chasanatusy; Gumilang, Retna; Bintarti, Tri Wahyuni (Jurnal Medis Islam Internasional, 2023)
Background: Borax can result in oxidative stress and cause the onset of gastrointestinal ulcerations that will dampen the duodenal villi to become shorter and can even disappear. Cell damage due to oxidative stress can be prevented by administering antioxidants. Antioxidants will inhibit the onset of chain reactions in the formation of free radicals by complementing the existing electron deficiency. Honey is one of the natural ingredients that is rich in antioxidants and part of thibbun Nabawi as one of the inhibitors of the toxic effects of borax. Objective : The purpose of this study is to to analyze the effect of honey administration on the histopathological description of submucosa and epithelial mucosa of duodenal wistar rats as an inhibitor of the toxic effects of borax (Sodium tetraborate). Methods: This study used the true experimental method with Post Test Only Control Group Design using 25 mice which will be divided into five groups, namely K (negative control), P (positive control), M1 (borax and honey dose 1), M2 (borax and honey dose 2), M3 (borax and honey dose 3). This study was conducted for 22 days then. Took the duodenal organ on all samples and then made histological preparations with HE staining. Observations were made with an Olympus microscope to see submucosal edema and damage to the epithelium of the duodenal mucosa. Results: The results of the study found that borax 26 mg / head / day had an influence on the histopathological picture of duodenal borax. In addition, the administration of honey dose 75 mg / Kg BB provides a toxic inhibitory effect of borax in the duodenum best among other treatment groups. However, statistically there was no effect of honey administration on the histopathological picture of the duodenum of wistar rats as an inhibitor of the toxic effect of borax (Sodium Tetraborate) with p˃0.05. Conclusion: Statistically it can be concluded that there is no effect of  the administration of honey on the histopathology picture of the duodenum of wistar rats as an inhibitor of the toxic effects of borax (Sodium tetraborate).